2020
DOI: 10.1186/s12284-020-00383-7
|View full text |Cite
|
Sign up to set email alerts
|

ATP Hydrolysis Determines Cold Tolerance by Regulating Available Energy for Glutathione Synthesis in Rice Seedling Plants

Abstract: Background: Glutathione (GSH) is important for plants to resist abiotic stress, and a large amount of energy is required in the process. However, it is not clear how the energy status affects the accumulation of GSH in plants under cold stress. Results: Two rice pure lines, Zhongzao39 (ZZ39) and its recombinant inbred line 82 (RIL82) were subjected to cold stress for 48 h. Under cold stress, RIL82 suffered more damages than ZZ39 plants, in which higher increases in APX activity and GSH content were showed in t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 110 publications
(124 reference statements)
5
25
1
Order By: Relevance
“…Substrate inhibition was also found at ATP concentrations exceeding 4 mM. If we convert literature data (25-35 nmol g −1 fw; e.g., Yu et al, 2020) into molar levels on the assumption of an intracellular volume (excluding vacuoles) equal to about 2-4% of the total water content in rice leaves, the concentration of ATP in the cell should range from 0.6 to 1.5 mM. It is therefore likely that such inhibition does not have a physiological role.…”
Section: Discussionmentioning
confidence: 99%
“…Substrate inhibition was also found at ATP concentrations exceeding 4 mM. If we convert literature data (25-35 nmol g −1 fw; e.g., Yu et al, 2020) into molar levels on the assumption of an intracellular volume (excluding vacuoles) equal to about 2-4% of the total water content in rice leaves, the concentration of ATP in the cell should range from 0.6 to 1.5 mM. It is therefore likely that such inhibition does not have a physiological role.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, maintaining energy homeostasis is a challenge for all living organisms under abiotic stress conditions, and an intimate relationship exists between energy availability and stress tolerance in plants ( De Block and Van Lijsebettens, 2011 ; Dröge-Laser and Weiste, 2018 ). The enhancement of antioxidant capacity and the accumulation of heat shock proteins are such energetically expensive processes that plant growth and development are inhibited, and plants may die if extreme stress lasts until an energy threshold is reached above which the damage can no longer be repaired ( Baena-González and Sheen, 2008 ; Yu et al, 2020 ). Plants with reduced poly(ADP-ribose) polymerase activity consumed less NAD(H) in stressful environments and improved their energy utilization efficiency by reducing overactive mitochondrial respiration and ROS production, thereby increasing stress tolerance ( Vanderauwera et al, 2007 ; Rissel et al, 2017 ; Jiang et al, 2020 ).…”
Section: High Energy Cost Of Maintenance Respiration Processes Under Moderate High-temperature Conditionsmentioning
confidence: 99%
“…Fatty acids offer an essential source of energy for life activities in plants [ 55 , 56 ], while adenosine phosphates, which are involved in ATP energy metabolism, supply a more straightforward energy utilization for plants [ 57 ]. It has also been suggested that fatty acid content and adenosine phosphates content change in a variety of plants under salt, low temperature or drought stress [ 58 , 59 , 60 , 61 , 62 ]. This indicates that adversity stress may cause changes in energy metabolism in different aspects.…”
Section: Introductionmentioning
confidence: 99%